Monetary Policy and Balance Sheets - Igan, Deniz (IMF Working Papers; Working Paper, 2013)
This paper evaluates the strength of the balance sheet channel in the U.S. monetary policy transmission mechanism over the past three decades. Using a Factor-Augmented Vector Autoregression model on an expanded data set, including sectoral balance sheet variables, we show that the balance sheets of various economic agents act as important links in the monetary policy transmission mechanism. Balance sheets of financial intermediaries, such as commercial banks, asset-backed-security issuers and, to a lesser extent, security brokers and dealers, shrink in response to monetary tightening, while money market fund assets grow. The balance sheet effects are comparable in magnitude to the traditional interest rate channel. However, their economic significance in the run-up to the recent financial crisis was small. Large increases in interest rates would have been needed to avert a rapid rise of house prices and an unsustainable expansion of mortgage credit, suggesting an important role for macroprudential policies.